2017
DOI: 10.1007/s10334-017-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatic fatty acid polyunsaturation precedes ectopic lipid deposition in the liver in adaptation to high-fat diets in mice

Abstract: A similar adaptation of hepatic lipids to both fasting and an HFD suggests common mechanisms of lipid trafficking from adipose tissue to the liver. Altered hepatic lipid handling with fasting indicates imperfect metabolic recovery from HFD exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…Mice were randomly split in three groups ( n = 11/group), and dietary interventions started after 1 week of acclimatization to the facility, i.e., at 3 months of age. During 6 months, mice were fed standardized diets containing 10%, 45%, or 60% of kilocalories from lard-based fat (D12450B, D12451, D12492, Research Diets, New Brunswick, NJ, United States), as previously detailed (Soares et al, 2018). Food and tap water were provided ad libitum .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were randomly split in three groups ( n = 11/group), and dietary interventions started after 1 week of acclimatization to the facility, i.e., at 3 months of age. During 6 months, mice were fed standardized diets containing 10%, 45%, or 60% of kilocalories from lard-based fat (D12450B, D12451, D12492, Research Diets, New Brunswick, NJ, United States), as previously detailed (Soares et al, 2018). Food and tap water were provided ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we tested the hypothesis that the severity of the metabolic syndrome is related to the degree of neurochemical alterations, as well as brain function deficits. For that, mice were fed diets containing different amounts of fat during 6 months, which lead to different degrees of glucose intolerance and insulin resistance (Soares et al, 2018). We then evaluated spatial memory performance, metabolic profiles of the hippocampus, cortex and hypothalamus, and levels of proteins specific to synaptic and glial compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in T2D animal models have employed diets rich in sugar and/or fat in order to induce T2D, namely, highfat diet (HFD), high-sucrose diet, high-fructose diet, or the combination of some of them. Glucose intolerance develops promptly in rodents exposed to HFD, followed by a progressive increase of fasting insulin levels and metabolic derangements such as hepatic lipid accumulation (Soares et al, 2018). We have also recently reported that increasing the dietary amount of lard-based fat from 10 to 45 or 60% leads to slightly different diabetic phenotypes: compared to controls that were exposed to the low-fat diet, increased fed glycemia and plasma corticosterone were observed in mice fed a 60%-but not 45%-fat diet (Lizarbe et al, 2019b).…”
Section: Memory Dysfunction Induced By Diabetogenic Dietsmentioning
confidence: 99%
“…Nevertheless, gene expression profiles in brain microvessels isolated from models of diabetes point toward deregulated expression of genes related to angiogenesis, inflammation, vasoconstriction and vasodilation, and platelet activation pathways (Rom et al, 2019). Proteomic analyses suggest impaired metabolic activity in microvessels from the cerebral cortex of HFD-exposed mice compared to controls (Ouyang et al, 2014), even though HDF exposure results in limited increases of blood glucose levels (Soares et al, 2018;Lizarbe et al, 2019b). Such alterations are likely to impact brain perfusion and to limit nutrient delivery for fueling neuronal energetics (Glaser et al, 2012;Bangen et al, 2018).…”
Section: Hyperglycemia and Brain Glucose Toxicitymentioning
confidence: 99%
“…(2 g/kg; prepared as 20% (w/v) solution in sterile saline, BRAUN, Melsungen, Germany). Glycaemia 6 was monitored with a glucometer (Accu-check Aviva, Roche, Stockholm, Sweden) from 1-µL tail tip blood samples before the glucose load, and afterwards at 15, 30, 60, 90 and 120 minutes (Soares et al, 2018). A 20-µL blood sample was collected from the saphenous vein for fasting insulin quantification (ELISA kit #10-1247-01 from Mercodia, Uppsala, Sweden).…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%